KEPEMIMPINAN YANG EFEKTIF DAN PERUBAHAN ORGANISASI (Fokus Ekonomi, 2008)
Leadership play role important in organization. Its success an organization is one of themdetermined by existing resource in the organization. Especial role of leadership is to influenceothers to reach target which have been specified. Leadership represents something that should bepossessed by each leader of an organization. The effectiveness of a leader is determined by hisability to influence and direct the members of an organization. The most effective leadership styleis leadership which is adapted to the situation of the people being led.K y words: leadership, organization, effectiveness.